Traditional practices during pregnancy and childbirth among tribal women from Maharashtra: a review - Begum, Shahina; Sebastian, Ajeesh; Kulkarni, Ragini; Singh, Shalini; Donta, Balaiah (International Journal Of Community Medicine And Public Health, 2017)
There are various traditional beliefs and practices exist in relation to pregnancy and childbirth among various tribal communities in Maharashtra. A review of published literature has conducted and a total of 114 articles and reports were reviewed out of which 14 articles and reports were eligible for the final review. Utilization of maternal and child health (MCH) services during pregnancy and delivery period was reportedly poor among tribal communities due to strong traditional beliefs and trust in Dai, and preference for home delivery for the requirement of some rituals performance. Unhygienic cord care practices, delay in initiation of breastfeeding, and no colostrum feeding practice were also observed. Culturally sensitive tailored interventions are required to influence the existing maternal and child health related traditional practices